Analisis Pengaruh Faktor-Faktor Produksi Terhadap Produkditivitas Usahatani Padi Sawah Pasang Surut di Desa Sungai Beringin Kecamatan Tembilahan Kabupaten Indragiri Hilir - Shelvi Sriyanti; Suardi Tarumun; Yusmini ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
As a strategic commodity, rice is a key sector to support regional development through agricultural sector. As a primary need, rice holds an important role at regional rice requirement fulfillment. The need of rice consumption is rising because of the population increase. In order to maintain its availability, the preservation of paddy cultivation is important to be done by considering agro-ecosystem, social, and culture condition, and people preference. At the same time rice productivity is getting difficult to increase. The area of rice field in Indragiri Hilir Regency in 2010 is about 36.444 Ha, and in Tembilahan Subdistrict where the research was done is about 2.200 Ha. The aims of this research are to analyse the influence of rice production factors on productivity and to determine the use of production factors to achieve the optimum production. This research uses Cobb Douglas's producton function to analyze the influence of these production factors on rice production. Respondents of 39 farmers are taken by simple random method. The research result shows that fertilizers, seeds, pesticide, and micro water ordinance variables have significant impact on productivity at 85,3% level. Keywords: Rice Farming, Cobb Douglas production function, productivity.